Multiple myeloma: disease response assessment. Issue 9 (1st September 2016) - Zamagni, E.; Tacchetti, P.; Terragna, C.; Cavo, M.
ABSTRACT: Precise assessment of response to therapy is of high importance in every phase of multiple myeloma (MM). In addition to the well-established role of monoclonal protein for clinical monitoring, several methods of minimal residual disease evaluation, both inside and outside the bone marrow (BM), are to date available. Next generation flow cytometry and sequencing are probably the best approaches at the BM level, being highly sensitive and uniformly applied. FDG PET/CT is the best imaging technique for evaluating and monitoring response to therapy outside the BM. Functional whole-body MRI techniques (DCE and DWI) seem promising for response evaluation and need further studies. Standardization of most of these techniques is in progress.